Effect of cultivar, packaging treatments and temperature on post-harvest quality of okra - Elkashif, Mohamed E.; Elamin, Osman M.; Alamri, Khalid M. (Gezira Journal of Agricultural Science; Vol 11 No 1 (2013), 2013)
ABSTRACT    Okra is one of the most popular vegetable crops in Sudan. The introduced cultivars such as Pusa Swani and Clemson Spineless have smooth pods and more adapted to the winter conditions of central Sudan. However, the local cultivar, Khartoumia, has hairy pods and not acceptable in international markets. Okra pods are highly perishable and subject to shriveling especially under the hot arid conditions of central Sudan. Therefore, the objective of this study was to determine the effect of packaging and temperature on the shelf life of okra pods of three introduced cultivars. Treatments consisted of three okra cultivars, namely, Clemson Spineless, Pusa Swani and Mahyco (hybrid); packaging treatments consisted of packing okra pods in cartons lined with intact polyethylene film, perforated polyethylene film or in cartons only and storage temperatures were 14 0 C and 32 0 C. Results showed that pods of the  cultivar Mahyco had the lowest weight loss, retained good colour and had the least decay and rot. Packaging of okra pods in intact or perforated polyethylene film and storing at 14 0 C reduced weight loss and resulted in the best pod colour compared to the control. Packaging in perforated polyethylene film and storing at 14 0 C resulted in the lowest incidence of decay and rot and best overall quality of pods. It is recommended to package okra pods in perforated polyethylene film and ship them to markets at 14 0 C.